Risk benefits of new ingredients added to novel cereal-based formulations - Mesias, Marta (2022)
The cereal-based food formulations has evolved in the last decades with the inclusion of alternative cereals, pseudocereals and other ingredients in traditional recipes, which allows current consumers’ needs to be met. The incorporation of ingredients such as seeds, legume flours or different type of sugars in the innovative formulation of biscuits may be particularly desirable from a nutritional and healthy point of view. However, the dough composition, low moisture and thermal treatment applied during baking can promote the formation of chemical process contaminants, such as acrylamide, which is classified as “probably carcinogenic for humans” [1]. The effect of addition of chia seeds, carob flour and coconut sugar on the nutritional and bioactive properties and the formation of acrylamide in wheat flour-based biscuits was investigated. Different biscuits were formulated replacing wheat flour by chia seeds (percentages in the final weight: 5, 10 and 15%) and carob flour (percentages in the final weight: 1, 5 and 10%) and white sugar by coconut sugar. Biscuit were prepared under controlled conditions and baked for 23 minutes at 180 ºC. Nutritional composition (AOAC methods), in vitro bioactivity (antioxidant capacity (TBARs), antibacterial and antifungal activity) and acrylamide content (HPLC-ESI-MS/MS) were determined in both ingredients and biscuits. Results were statistically analyzed using SPSS version 26 (SPSS, Chicago, IL, USA) assuming a level of significance of p < 0.05. Higher percentages of chia seeds, carob flour and coconut sugar in the formula exhibited similar antibacterial and antifungal activity to the control biscuit (100% wheat flour, 100% white sugar) but increased the antioxidant capacity, protein, fiber and, in the case of chia seeds, the polyunsaturated fatty acids content, then resulting in a nutritionally enhanced product. However, levels of acrylamide were also increased, from 113 to 236 μg/kg, when chia seeds were added in a range of 5-15% of the total weight and reaching values up to 351 μg/kg when carob flour was incorporated in a 10% or even to 1030 μg/kg when biscuit containing 10% carob flour were also formulated with coconut sugar. In these cases, acrylamide concentrations exceeded the benchmark levels (350 μg/kg) established for biscuits in the European Regulation 2158/2017 [2]. This study suggests that the reformulation of traditional recipes with innovative ingredients should be carefully considered, not only looking for nutritionally improved recipes but also taking into account possible changes in the toxicological aspects. To this end, it should be recommended to include a risk/benefit evaluation of the control of process contaminants when designing novel biscuit formulas.